Avaliação do espectro harmônico da corrente de um conjunto de cargas não lineares monofásicas por matrizes de admitâncias complexas - Renato Jose Senra Barbosa (2017)
The problem of computing the harmonic currents produced by nonlinear loads has been constantly raised in the field of power quality. Such a problem becomes even more difficult when the voltage supply has already been polluted with harmonics. The effect of harmonic polluted voltage supply is addressed in this work by presenting measurement results showing how the harmonic currents generated by a nonlinear load can depend on the distortion parameters of the voltage supply. Upon posed the problem of harmonic currents dependency on the voltage supply pollution, this work seeks an adequate representation for nonlinear loads in this context. When dealing with the representation of a nonlinear load through admittances, whose magnitude and angle depend on the harmonic content of the supply voltage, the tensor based procedures are accurate enough when the load admittance loci yields to a circle, which is usually the case for simulations. However, this modeling approach does not fit all types of loads. To account for the admittance variation due to the dependency on the supply voltage angle (fundamental and harmonics), this work introduces a special procedure involving a collection of admittance matrices, which is suitable for any load modeling, as it can use data even from measurement, which may reveal all nonlinear behavior of real loads. The method is based on the iterative calculation using an updated Norton admittance, which takes into account the magnitude and angle voltage dependency behavior of the nonlinear load. Once the parameters from the electrical system and loads are gathered, the method provides a deterministic way of assessment the line current produced by as single load or a group of these specific loads. Besides the mentioned measurements, numerical calculations comparing results from time-domain simulation and the proposed methodology are presented for validation purposes. The developed procedure is also used to compute the total current for two sets of different loads connected to the same feeder, showing its applicability to more general cases